2014
DOI: 10.1002/gps.4161
|View full text |Cite
|
Sign up to set email alerts
|

Apathy as a feature of prodromal Alzheimer's disease: an FDG‐PET ADNI study

Abstract: The presence of apathy in MCI patients is associated with AD-specific pattern of brain metabolic defect. These results could suggest that apathy belongs to the spectrum of prodromal AD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 56 publications
3
40
0
1
Order By: Relevance
“…[59] Numerous studies have identified apathy as an early and common behavioral symptom in MCI and AD dementia linked to clinical progression[59, 60] and, recently, to posterior cingulate cortex hypometabolism in amnestic MCI. [61] Our current findings suggest that apathy and anhehonia may also signal early neurodegeneration and, thereby, increased vulnerability to clinical decline, in CN elderly. Apathy-andedonia factor scores in our sample were also significantly associated with high amyloid burden in unadjusted bivariate analyses, implicating AD pathophysiology, and in line with evidence of an association of greater apathy with high amyloid at the stage of MCI.…”
Section: Discussionmentioning
confidence: 75%
“…[59] Numerous studies have identified apathy as an early and common behavioral symptom in MCI and AD dementia linked to clinical progression[59, 60] and, recently, to posterior cingulate cortex hypometabolism in amnestic MCI. [61] Our current findings suggest that apathy and anhehonia may also signal early neurodegeneration and, thereby, increased vulnerability to clinical decline, in CN elderly. Apathy-andedonia factor scores in our sample were also significantly associated with high amyloid burden in unadjusted bivariate analyses, implicating AD pathophysiology, and in line with evidence of an association of greater apathy with high amyloid at the stage of MCI.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly apathy is associated with decreased perfusion in ACC (Benoit et al, 2004; Lanctôt et al, 2007; Robert et al, 2006), decreased ACC white matter integrity by DTI (Hahn et al, 2013; Kim et al, 2011; Ota et al, 2012) and increased amyloid burden in right ACC (Mori et al, 2014). Apathy is also associated with decreased PCC metabolism (Delrieu et al, 2015). There are also links between apathy and volume loss and/or cortical thinning in frontal cortex (Apostolova et al, 2007; Bruen et al, 2008; Stanton et al, 2013; Tunnard et al, 2011), though there is no strict concordance on the specific regions of frontal cortex which include medial, lateral, and orbital regions.…”
Section: Resultsmentioning
confidence: 99%
“…Many data established a possible link between apathy and AD with a decreased reliability of ACC network, mainly due to an increased generalized amyloid depositions (Canevelli et al, 2013), a volume loss in ACC (Apostolova et al, 2007; Bruen et al, 2008; Marshall et al, 2013; Stanton et al, 2013), a decreased perfusion in ACC (Benoit et al, 2004; Lanctôt et al, 2007; Tunnard et al, 2011), a decreased ACC white matter related integrity (Robert et al, 2006; Kim et al, 2011; Hahn et al, 2013), and increased amyloid burden in right ACC (Ota et al, 2012; Mori et al, 2014). Apathy is also associated with decreased posterior cingulate (PCC metabolism; Migneco et al, 2001), with a reduced insular volume (Moon et al, 2014a; Delrieu et al, 2015), and with decreased inferior temporal cortical (ITC) thickness (Moon et al, 2014b; Guercio et al, 2015), with cortical shrinkage of the frontal cortex (Apostolova et al, 2007; Bruen et al, 2008; Marshall et al, 2013; Stanton et al, 2013), with greater amyloid burden in bilateral frontal cortex (Ota et al, 2012), reduced orbitofrontal metabolism on the left (Donovan et al, 2014) or right (Benoit et al, 2004), and reduced connectivity in left-sided functional connectivity, with thalamus and parietal cortex, and amygdala (Holthoff et al, 2005; Kang et al, 2012; Ota et al, 2012; Baggio et al, 2015). Galantamine, as a cholinesterase inhibitor has been linked to a slower decrease of the putamen metabolism (Zhao et al, 2014), based on FDG-PET study (Zhao et al, 2014).…”
Section: What Do We Know About Apathy From Clinical Practice?mentioning
confidence: 99%
“…Data are not univocal (Donovan et al, 2014; Delrieu et al, 2015). One fMRI study found alterations in functional limbic-hypothalamic networks in relation to apathy (Tatemichi et al, 1992; Starkstein et al, 1997; Balthazar et al, 2014).…”
Section: What Do We Know About Apathy From Clinical Practice?mentioning
confidence: 99%